Perancangan Palang Pintu Otomatis Dilengkapi Pengecekan Suhu Dan Hand Sanitizer Menggunakan Arduino Berbasis Internet of Things Pada SDN Parakan Kota Tangerang Selatan - Tasha Eka Putri; Ari Mulyoto (CV. Multi Kreasi Media, 2023)
Implementation of the Covid-19 protocol, checking body temperature manually using a thermo gun or thermal scanner can cause long queues and crowds. In addition, checking body temperature in this way can endanger officers because there is still a possibility that one of the people having their temperature checked will carry Covid-19. The automatic doorstop prototype using a temperature sensor is an innovation where the doorstop has a MLX90164 non-contact temperature sensor which can carry out temperature readings for everyone who wants to enter the school area. The tool can read the body temperature of someone who is in front of the sensor. This tool is also equipped with an automatic hand sanitizer so that it can keep everyone who wants to enter the school area clean and sterile. With a few modifications, this automatic doorstop using a temperature sensor can be applied to school areas throughout Indonesia to implement the Covid-19 health protocol more effectively.